HOW TO MEASURE THE LARGEST BASAL DIMENSION OF CHOROIDAL MELANOMA: A MATHEMATICAL STUDY. Issue 11 (November 2019) - França, Maira; Ayres, Bernadete; Parrish, Elizabeth; Demirci, Hakan
Abstract : Purpose: To identify the most accurate ultrasonographic technique to measure the largest basal dimension (LBD) of choroidal melanoma. Methods: B-scan ultrasound images were retrospectively reviewed in 99 eyes of 99 choroidal melanoma patients. The LBD was measured using one, two, and three straight lines along the inner and outer sclera. Theoretical arc length, calculated using trigonometry formulas based on the spherical model with the axial length as the sphere diameter, was used for comparisons with the actual measurements using straight lines. Results: For straight-line measurements in the inner sclera, the lowest error was found when using two straight-line measurements ( P = 0.118). Differences in measurement using one-segment or three-segment measurements as compared with the theoretical arc length were found to be statistically significant ( P < 0.001 in both cases). For tumors with LBD smaller than 12 mm, the absolute error, compared with the theoretical arc length, was smaller than 1 mm. In the outer sclera, the smallest errors were also found for measurements using two straight-line segments; however, it was statistically different than the theoretical inner arc length ( P < 0.001). Conclusion: When using ultrasound to estimate LBD of ocular tumors, 2 straight-line measurements should be used when LBD is larger than 12 mm. For tumors with LBD smaller than 12 mm, measurements using 1 straight-line segment can provide accurate estimates. Abstract : This study investigated the accuracy of measurements of the largest basal dimension of choroidal melanoma using ophthalmic ultrasound. The larger the tumor, the less accurate is the estimate, and this study provides a practical method to use either two-chord measurements or using a software application.